Tratamento de efluentes de lavanderia hospitalar para fins de reuso - Souza, Renata Cristina de (2012)
Amongst the different hospital wards, the one which is more relevant concerning the effluents generation is the hospital laundry. These effluents are one of the most meaningful causes of environmental damage due to their characteristics, such as the presence of pathogenic microorganisms, sanitizers, disinfectants, antibiotics, cleansing agents and other surfactants. The advanced oxidation processes have been used in the treatment of effluents, with the advantage of destroying the contaminants instead of just transferring them in phase. The use of ultraviolet (UV) radiation has been assessed in the treatment of effluents aiming, mainly, at its disinfection. In addition to that, the UV radiation combined with hydrogen peroxide (UV/H2O2) has been used in the treatment of residuary water aimed at the reuse, which allows to the disinfection and degradation of organic compounds, being a process with little addition of chemical products and easy to operate. Coagulation/flocculation has been used both as pretreatment and post-treatment of effluents, and it promotes the formation of aggregates in the effluents reducing the concentration of pigments. Thus, this paper aimed at assessing the treatment of effluents of hospital laundry, using UV, UV/H2O2 radiation and process combined with UV/H2O2 and coagulation/flocculation/sedimentation, for the production of water for reuse. In order to do that, samples of effluents were collected at a hospital laundry for the physical-chemical and microbiological characterization and the performing of photooxidation treatment in bench scale. A cylindrical reactor was used for these assays, having a useful volume of 500 ml, with an immersed lamp (10w). The results of the assays that only used UV radiation have shown that there was a reduction of pathogenic microorganisms after 30 minutes of reaction, and a reduction of up to 60% of the surfactants in 60 minutes. The UV/H2O2 process, in the great condition with pH 9 and ratio [COD:H2O2] 1:2,5, reduced in 63% the COD and 99% the surfactants, however the process was not efficient in the reduction of color and turbidity. In the coagulation/flocculation/sedimentation assays using chemical and natural coagulants, the best concentration was of 600 mg/L for reduction of color and turbidity, although the natural coagulant Tanfloc presented a smaller amount of sludge generated in the process. In the tests combined of coagulation/flocculation/sedimentation using the natural coagulant Tanfloc SG and UV/H2O2 in the great condition, it was possible to meet the characteristics of water aimed at reuse.